(untitled) (Academicia Globe: Inderscience Research, 2022)
Oratory is a complex field in the methodology of sciences that has been studied both as an art and as a branch of science. In this article, the social direction, features and linguistic aspects of this field has been clarified. The specific linguistic units of the art of oratory, the history of its means, namely, the elements that give rise to oratory skills are discussed.